2006
DOI: 10.1080/09603120500397680
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between changes in daily air pollution and hospitalizations in Perth, Australia 1992–1998: A case-crossover study

Abstract: A case-crossover study was undertaken to investigate the relationship between daily air pollutant concentrations and daily hospitalizations for selected disease categories in Perth, Western Australia. Daily measurements of particles (measured by nephelometry and PM2.5), photochemical oxidants (measured as ozone), nitrogen dioxide (NO2) and carbon monoxide (CO) concentrations were obtained from 1992 to 1998 via a metropolitan network of monitoring stations. Daily PM2.5 concentrations were estimated using monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…Some authors described significant increases of numbers of hospital admissions (Luginaah et al, 2005;Zanobetti and Schwartz, 2006). Other authors found small but significant effects of CO on respiratory hospitalizations (Fusco et al, 2001;Hinwood et al, 2006;Sauerzapf et al, 2009), could also not see significant effects (Fung et al, 2006), or detected protecting effects of CO for respiratory tract infections at lower concentration levels (Tian et al, 2013).…”
Section: Comentioning
confidence: 91%
“…Some authors described significant increases of numbers of hospital admissions (Luginaah et al, 2005;Zanobetti and Schwartz, 2006). Other authors found small but significant effects of CO on respiratory hospitalizations (Fusco et al, 2001;Hinwood et al, 2006;Sauerzapf et al, 2009), could also not see significant effects (Fung et al, 2006), or detected protecting effects of CO for respiratory tract infections at lower concentration levels (Tian et al, 2013).…”
Section: Comentioning
confidence: 91%
“…The case-crossover design has been applied in numerous studies to investigate the acute effects of air pollution, including mortality, 13 cardiovascular events, 14-33 and respiratory outcomes. 24,[34][35][36][37][38][39][40] We constructed time-stratified, 41 casecrossover datasets, using 28-day strata. Within a stratum, each case event (an ED visit) was matched to exactly three referent times matched on the same day of the week: that is, at ±7, ±14, and ±21 days.…”
Section: Conceptual Framework and Analysismentioning
confidence: 99%
“…An association between daily ozone levels and respiratory symptoms has been reported (Romieu et al, 1996;Rabinovitch et al, 2004). Nevertheless, some authors have failed to note a significant relationship between ozone levels and morbidity (Atkinson et al, 1999;Farhat et al, 2005;Hinwood et al, 2006). Such differences are probably due to geographic reasons, although they may also be linked to the type of methodology employed.…”
Section: Introductionmentioning
confidence: 85%